Racial and ethnic differences in hospice enrollment among children with cancer. Issue 10 (3rd June 2013) - Thienprayoon, Rachel; Lee, Simon Craddock; Leonard, David; Winick, Naomi
Abstract Background Hospice is an important provider of end of life care. Adult minorities are less likely to enroll on hospice; little is known regarding the prevalence of pediatric hospice use or the characteristics of its users. Our primary objective was to determine whether race/ethnicity was associated with hospice enrollment in children with cancer. We hypothesized that minority (Latino) race/ethnicity is negatively associated with hospice enrollment in children with cancer. Procedure In this single‐center retrospective cohort study, inclusion criteria were patients who died of cancer or stem cell transplant between January 1, 2006 and December 31, 2010. The primary outcome variable was hospice enrollment and primary predictor was race/ethnicity. Results Of the 202 patients initially identified, 114 met inclusion criteria, of whom 95 were enrolled on hospice. Patient race/ethnicity was significantly associated with hospice enrollment (P = 0.02), the association remained significant (P = 0.024) after controlling for payor status (P = 0.995), patient diagnosis (P = 0.007), or religion (P = 0.921). Latinos enrolled on hospice significantly more often than patients of other races. Despite initial enrollment on hospice however, 34% of Latinos and 50% of non‐Latinos had withdrawn from hospice at the time of death (P = 0.10). Race/ethnicity was not significantly associated with dying on hospice. Conclusions These results indicate that race/ethnicity and diagnosis are likely to play a role in hospice enrollment during childhood. A striking number of patients of all race/ethnicities left hospice prior to death. More studies describing the impact of culture on end of life decision‐making and the hospice experience in childhood are warranted. Pediatr Blood Cancer 2013;60:1662–1666. © 2013 Wiley Periodicals, Inc.